Switzerland : an international banking and finance center - Iklé, Max. (Stroudsburg, Pa. : Dowden, Hutchinson & Ross, 1972)
The book is discussed under three sections. Section 1 is the study of the origin of development of Switzerland banking center. The second section goes to explain postwar policies in the areas of currency, finance, and business cycle, with particular attention to investment bank cooperation. While the third section, highlights the current structure of the Swiss banking and financial center.
Translation of Die Schweiz als internationaler Bank- und Finanzplatz.
Includes bibliographical footnotes
usc 17/05/2018
Loans
Keywords: Banks and banking; Banks and banking, International; Switzerland